Description of stress–strain curves for stainless steel alloys. (15th December 2015) - Arrayago, I.; Real, E.; Gardner, L.
Abstract: There is a wide variety of stainless steel alloys, but all are characterized by a rounded stress–strain response with no sharply defined yield point. This behaviour can be represented analytically by different material models, the most popular of which are based on the Ramberg–Osgood formulations or extensions thereof. The degree of roundedness, the level of strain hardening, the strain at ultimate stress and the ductility at fracture of the material all vary between grades, and need to be suitably captured for an accurate representation of the material to be achieved. The aim of the present study is to provide values and predictive expressions for the key parameters in existing stainless steel material models based on the analysis of a comprehensive experimental database. The database comprises experimental stress–strain curves collected from the literature, supplemented by some tensile tests on austenitic, ferritic and duplex stainless steel coupons conducted herein. It covers a range of stainless steel alloys, annealed and cold-worked material, and data from the rolling and transverse directions. In total, more than 600 measured stress–strain curves have been collected from 15 international research groups. Each curve from the database has been analysed in order to obtain the key material parameters through a curve fitting process based on least squares adjustment techniques. These parameter values have been compared to those calculated from existing predictive models, the accuracy of which could therefore be evaluated. Revised expressions providing more accurate parameter predictions have been proposed where necessary. Finally, a second set of results, containing material parameters reported directly by others, with information of more than 400 specimens, has also been collected from the literature. Although these experimental results were not accessible as measured raw data, they enabled further confirmation of the suitability of the proposed equations. Graphical abstract: Highlights: Tensile tests on austenitic, ferritic and duplex stainless steel coupons are presented. A database of over 600 stainless steel stress–strain curves has been collected. Key material parameters for different stainless steel families have been obtained. Existing equations for the determination of material parameters have been assessed. Revised expressions providing more accurate material parameter predictions have been proposed and verified.